Influence of Kappa Number on Enhancing Pulp Brightness through Stage D0 with ClO2 Bleaching Process: Environmental Implications and Considerations - Susi Susanti (ENVIRO: Journal of Tropical Environmental Research, 2024)
Stage D0 in the pulp bleaching process, utilizing Chlorine Dioxide (ClO2), represents a critical phase aimed at improving pulp brightness while simultaneously addressing environmental concerns. This stage enhancement of pulp brightness can made an environmental impact, as excessive usage can lead to harmful emissions and environmental degradation. The amount of ClO2 used at stage D0 is influenced by the kappa number, the greater the kappa number, the greater the ClO2 use will be to produce brightness that corresponds to standar. The calculation of ClO2 usage at stage D0 is carried out after obtaining data related to ClO2 and the amount of pulp production from DCS (Distribute Control System). Based on the results of calculations and analysis, it can be concluded that the kappa number influences the total use of ClO2 in stage D0. The more ClO2 used in the D0 tower will produce pulp with a higher level of brightness.